UMKM Hijau Dan Berdaya Saing: Optimalisasi Transformasi Digital Sebagai Upaya Inovasi Berkelanjutan - Fauziah, Fadhilah Ayu Rohmatil; Hasibuan, Lempang; Salsabila, Aisyah; Indah, Ana Nur (Jurnal E-Bis, 2025)
Kalimantan's economy is currently mostly supported by the coal sector. The global economic trend is moving towards a green economy, meaning coal is expected to decrease gradually. For this reason, MSMEs are one of the businesses that can help Kalimantan's economy in the future. This research uses literature study, namely by reviewing and analyzing all information regarding the research topic. Researchers used fifty articles that had been reviewed using Sinta, Scopus, and Google Scholar. Zed's theory, (2008) was used to obtain research results. The results of this research are that MSMEs can play an important role in encouraging and developing the Indonesian economy. MSMEs are an important element in creating a green economy in Indonesia. There are several problems faced by MSMEs, so digital transformation and sustainable innovation can be used as the right idea to increase competition towards the global market. The linkage of digital technology in green MSME activities is a solution and idea to increase competitive advantage as a competitive advantage for green MSMEs in the global market.